Chemical Synthesis and Characterization of Magnetic Iron (Fe3O4) Nanoparticles Used in Catalytic Decomposition of Hydrogen Peroxide - Danbature W. L; Isyaka, M. Sani; M. Abdullahi, Abdullahi.; Abdulmalik S. S (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Magnetic nanoparticles are rapidly piquing researchers due to their numerous uses such as catalysis, magnetism, medicine, optics, antibacterial, antifungal, and larvicidal treatments, Magnetic drug targets, magnetic resonance imaging for clinical diagnosis and recording material. This paper focuses on synthesis, characterization and study of magnetic iron (Fe3O4) nanoparticle’s catalytic properties in the decomposition of hydrogen peroxide as well as determination of reaction’s order. In the current study, co-precipitation was used to create magnetic iron (Fe3O4) nanoparticles as a result of surface Plasmon absorptions, the reaction mixture's hue changed, indicating the production of magnetic nanoparticles. FTIR spectra of Fe3O4 nanoparticle revealed the presence of peaks at 3420 cm-1, 2925 cm-1 and 500 cm-1 that corresponds to hydroxyl groups (O-H), CH3 stretching vibration and Fe-O stretching vibrations on the surface of the Fe3O4 nanoparticle. The UV-result of synthesized Fe3O4 nanoparticles showed the highest peak at 300 nm due to the excitation of electrons and d-d transition ability of the metal in question. This confirms that particles were stable and well dispersed in the solution. The XRD result revealed five main diffraction peaks at 2Ɵ =30°, 37 .6°, 49.3°, 54°, 57.1°, that corresponds to the planes (220, 311, 400, 422, and 511 respectively) of Fe3O4 nanostructures. The average crystallize size of Fe3O4 was determined using Debye-Scherer relation D=Kλ/βcosθ, and found to be 35.2 nm. Catalytic decomposition of hydrogen peroxide was carried out in an exothermic reaction in which hydrogen peroxide transforms into oxygen and water. Gasometric measurements was used to introduce various amounts of Fe3O4 catalyst to each reaction vessel containing hydrogen peroxide. The amount of oxygen evolved was measured on a regular basis and was observed that an increase in catalyst concentration sped up the reaction and reduced the amount of time needed for hydrogen peroxide to decompose. As a result, more oxygen gas was produced during the reaction as catalyst concentration increased. Therefore, the co-precipitation approach of creating nanoparticles is seen to be the best in terms of affordability, non-toxic nature, and uses environmentally acceptable chemicals. In the end, the decomposition of hydrogen peroxide (H2O2) was first order in relation to the catalyst concentration.